Heterozygous variants in the teashirt zinc finger homeobox 3 (TSHZ3) gene in human congenital anomalies of the kidney and urinary tract - Kesdiren, Esra; Martens, Helge; Brand, Frank; Werfel, Lina; Wedekind, Lukas; Trowe, Mark-Oliver; Schmitz, Jessica; Hennies, Imke; Geffers, Robert; Gucev, Zoran; Seeman, Tomáš; Schmidt, Sonja; et al. (European journal of human genetics, 2025)
Around 180 genes have been associated with congenital anomalies of the kidney and urinary tract (CAKUT) in mice, and represent promising novel candidate genes for human CAKUT. In whole-exome sequencing data of two siblings with genetically unresolved multicystic dysplastic kidneys (MCDK), prioritizing variants in murine CAKUT-associated genes yielded a rare variant in the teashirt zinc finger homeobox 3 (TSHZ3) gene. Therefore, the role of TSHZ3 in human CAKUT was assessed. Twelve CAKUT patients from 9/301 (3%) families carried five different rare heterozygous TSHZ3 missense variants predicted to be deleterious. CAKUT patients with versus without TSHZ3 variants were more likely to present with hydronephrosis, hydroureter, ureteropelvic junction obstruction, MCDK, and with genital anomalies, developmental delay, overlapping with the previously described phenotypes in Tshz3-mutant mice and patients with heterozygous 19q12-q13.11 deletions encompassing the TSHZ3 locus. Comparable with Tshz3-mutant mice, the smooth muscle layer was disorganized in the renal pelvis and thinner in the proximal ureter of the nephrectomy specimen of a TSHZ3 variant carrier compared to controls. TSHZ3 was expressed in the human fetal kidney, and strongly at embryonic day 11.5-14.5 in mesenchymal compartments of the murine ureter, kidney, and bladder. TSHZ3 variants in a 5' region were more frequent in CAKUT patients than in gnomAD samples (p < 0.001). Mutant TSHZ3 harboring N-terminal variants showed significantly altered SOX9 and/or myocardin binding, possibly adversely affecting smooth muscle differentiation. Our results provide evidence that heterozygous TSHZ3 variants are associated with human CAKUT, particularly MCDK, hydronephrosis, and hydroureter, and, inconsistently, with specific extrarenal features, including genital anomalies.
Keywords: Animals; Kidney; multicystické dysplastické ledviny; heterozygot; močové ústrojí; Female; Multicystic Dysplastic Kidney; Infant; předškolní dítě; dítě; transkripční faktory; ženské pohlaví; lidé; Heterozygote; Mice; urogenitální abnormality; Transcription Factors; homeodoménové proteiny; Urogenital Abnormalities; Mutation, Missense; myši; Vesico-Ureteral Reflux; missense mutace; Male; kojenec; Child, Preschool; Urinary Tract; Homeodomain Proteins; Child; mužské pohlaví; zvířata; ledviny; Humans